2015
DOI: 10.1074/jbc.m114.619007
|View full text |Cite
|
Sign up to set email alerts
|

The Short Stature Homeobox 2 (Shox2)-bone Morphogenetic Protein (BMP) Pathway Regulates Dorsal Mesenchymal Protrusion Development and Its Temporary Function as a Pacemaker during Cardiogenesis

Abstract: Background: Dorsal mesenchymal protrusion (DMP) is required for cardiac septation, but its additional functions are unknown. Results: Shox2 is required for the nodal-like characteristics and development of embryonic DMP by regulating BMP/Smad4 signaling pathway. Conclusion: A Shox2-BMP genetic cascade regulates DMP development and its temporal pacemaking function. Significance: A novel function of DMP and its developmental regulatory mechanism are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 51 publications
6
31
1
2
Order By: Relevance
“…AVJ develops from the dorsal mesenchymal protrusion, cushion septum tissues and the AVC-originating myocardium, including AVN progenitor cells (Munshi 2012;Ionta et al 2015). In contrast to the previous opinion that Shox2 expression is specifically distributed in the SAN and its precursor tissues, Shox2 is also expressed in the dorsal mesenchymal protrusion tissues and AVJ during embryonic development (Sun et al 2015). Pacemaker cell-specific expression levels of Hcn4 and Tbx3 genes and SAN-like electrophysiological characteristics have been identified in the Shox2 + dorsal mesenchymal protrusion tissues and gradually disappear with the maturation of the AVN.…”
Section: The Effect Of the Shox2 Gene In The Atrioventricular Conductcontrasting
confidence: 46%
See 1 more Smart Citation
“…AVJ develops from the dorsal mesenchymal protrusion, cushion septum tissues and the AVC-originating myocardium, including AVN progenitor cells (Munshi 2012;Ionta et al 2015). In contrast to the previous opinion that Shox2 expression is specifically distributed in the SAN and its precursor tissues, Shox2 is also expressed in the dorsal mesenchymal protrusion tissues and AVJ during embryonic development (Sun et al 2015). Pacemaker cell-specific expression levels of Hcn4 and Tbx3 genes and SAN-like electrophysiological characteristics have been identified in the Shox2 + dorsal mesenchymal protrusion tissues and gradually disappear with the maturation of the AVN.…”
Section: The Effect Of the Shox2 Gene In The Atrioventricular Conductcontrasting
confidence: 46%
“…Until E11.5, the Shox2 gene-expressing region expands to two parallel fascicular zones crossing the atrium vertical axis formed by SAN and venous valves, and these regions will constitute an indivisible part of CCS later. Simultaneously, Shox2 is expressed in the mouse AVJ and the upper part of ventricles, forming the left and right bundle branches (Sun et al 2015) (Fig. 3).…”
Section: The Shox2 Gene and Distribution Of Its Expressionmentioning
confidence: 99%
“…Studies revealed that the SHOX gene regulates main body structure development in the early embryo, especially the development and maturation of limb skeleton [27][28][29][30][31]. Recent evidence suggested that the SHOX gene plays important roles in the development of the sinus venosus and sinoatrial node (SAN) and is, therefore, crucial for the formation of the cardiac autonomic rhythm system [32][33][34]. In addition, it was also suggested that the SHOX gene is related to mechanosensory and palate development [35,36].…”
Section: The Function Of Shoxgenementioning
confidence: 97%
“…1) (2). To differentiate between the DMP prior to muscularization (which occurs from approximately embryonic day (E)13 in mouse) and other structures in the AV junction (AVJ) during early development, stainings of myocardial markers are essential, which are lacking in the paper by Sun et al (1). In our opinion, the 3 and 4).…”
mentioning
confidence: 97%
“…Sun et al (1) report that the dorsal mesenchymal protrusion (DMP) acts as a temporary pacemaker during early development, prior to formation of the atrioventricular node (AVN). We would like to question whether the anatomical designation of the DMP used in this paper is correct.…”
mentioning
confidence: 99%